PENGARUH KREATIVITAS DAN KEMUDAHAN PENGGUNAAN CANVA TERHADAP PEMBUATAN KONTEN DI INSTAGRAM - Haidar Musyaffa; Willia Ismiyarti (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2026)
The advancement of digital creativity encourages individuals to produce designs using applications that enhance both creativity and convenience. This study aims to analyze the influence of Creativity and Ease of Use of Canva on Content Creation on Instagram. This study employs a quantitative approach, utilizing purposive sampling as the data collection technique. The respondent criteria consisted of individuals who have previously used Canva for content creation purposes. The findings indicate that Ease of Use has a positive and significant effect on Content Creation on Instagram, whereas Creativity does not demonstrate a positive or significant effect partially. Simultaneously, both Creativity and Ease of Use have a significant combined effect on Content Creation on Instagram. These findings suggest that Content Creation is more strongly influenced by the perceived comfort in operating digital design applications than by creativity alone. This is consistent with real-world conditions, where users tend to prefer design applications that are easy to use, offer clear navigation, and provide straightforward features, thereby enhancing comfort, efficiency, and overall user experience in fulfilling their design needs.